Implementation of Road Infrastructure Development Policy in East Kolaka, Southeast Sulawesi - Rika Puspita; Abdul Juli Andi Gani; Shobaruddin, Muhammad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Road infrastructure development is a key factor in driving economic growth and improving the quality of life of people in the regions. East Kolaka Regency, as a developing region, faces challenges in implementing road development policies. The method used was descriptive qualitative research. Data were collected through observation and interviews. Data analysis was conducted using a thematic approach through several stages, starting from understanding the data to producing a report. The results showed that policy implementation was influenced by administrative regulations and problem-solving strategies. National regulations are the main reference in technical aspects, while regional policies focus on prioritizing according to local needs. Various strategies are applied to overcome challenges, such as data-based planning, community participation, phased development, bureaucratic reform, institutional collaboration, and structured monitoring. Although an action plan has been developed, it is still necessary to strengthen institutional capacity, optimize financial resources, improve data-based monitoring, and integrate sustainability principles